My CPSE-HSE Scholarship Journey - Bughio, Hira (Journal of Pakistan Psychiatric Society, 2022)
I graduated from Fatima Jinnah Medical College, Lahore in 2016 and in January 2018, I started my FCPS-II training in Psychiatry at Department of Psychiatry and Behavioral Sciences, Jinnah Postgraduate Medical Centre, Karachi under the supervision of Meritorious Prof. Muhammad Iqbal Afridi.